Development of a polar direct drive platform for mix and burn experiments on the National Ignition Facility. (March 2016) - Murphy, T J; Kyrala, G A; Krasheninnikova, N S; Bradley, P A; Cobble, J A; Tregillis, I L; Obrey, K A D; Baumgaertel, J A; Hsu, S C; Shah, R C; Hakel, P; Kline, J L; et al.
Abstract: Capsules driven with polar drive [1, 2] on the National Ignition Facility [3] are being used [4] to study mix in convergent geometry. In preparation for experiments that will utilize deuterated plastic shells with a pure tritium fill, hydrogen-filled capsules with copper- doped deuterated layers have been imploded on NIF to provide spectroscopic and nuclear measurements of capsule performance. Experiments have shown that the mix region, when composed of shell material doped with about 1% copper (by atom), reaches temperatures of about 2 keV, while undoped mixed regions reach about 3 keV. Based on the yield from these implosions, we estimate the thickness of CD that mixed into the gas as between about 0.25 and 0.43 μ m of the inner capsule surface, corresponding to about 5 to 9 μ g of material. Using 5 atm of tritium as the fill gas should result in over 10 13 DT neutrons being produced, which is sufficient for neutron imaging [5].